2019
DOI: 10.3389/fneur.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Recordings Reveal Transient Increase of Alpha/Low-Beta Power in the Subthalamic Nucleus Associated With the Onset of Parkinsonian Rest Tremor

Abstract: Functional magnetic resonance imaging studies suggest that different subcortico-cortical circuits control different aspects of Parkinsonian rest tremor. The basal ganglia were proposed to drive tremor onset, and the cerebellum was suggested to be responsible for tremor maintenance (“dimmer-switch” hypothesis). Although several electrophysiological correlates of tremor have been described, it is currently unclear whether any of these is specific to tremor onset or maintenance. In this study, we present data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 44 publications
(54 reference statements)
2
25
2
Order By: Relevance
“…While tremor has previously been found to decrease β coherence between STN and motor cortex (Qasim et al, 2016) while increasing θ coherence (Hirschmann et al, 2013), we demonstrated directed θ phase interactions from STN to motor cortex specifically during tremor onset. While a previous case study of tremor onset displayed local STN and cortical α/β power changes with tremor onset (Hirschmann et al, 2019), we show here that STN and motor cortical θ activity are directionally linked. We also demonstrated that during sustained tremor, the STN-motor cortex θ phase slope relationship reversed, suggesting the θ influence over sustained tremor shifted source from STN to cortex.…”
Section: Discussioncontrasting
confidence: 66%
“…While tremor has previously been found to decrease β coherence between STN and motor cortex (Qasim et al, 2016) while increasing θ coherence (Hirschmann et al, 2013), we demonstrated directed θ phase interactions from STN to motor cortex specifically during tremor onset. While a previous case study of tremor onset displayed local STN and cortical α/β power changes with tremor onset (Hirschmann et al, 2019), we show here that STN and motor cortical θ activity are directionally linked. We also demonstrated that during sustained tremor, the STN-motor cortex θ phase slope relationship reversed, suggesting the θ influence over sustained tremor shifted source from STN to cortex.…”
Section: Discussioncontrasting
confidence: 66%
“…Stein and Bar-Gad [14] suggest that perhaps a single physiologically important oscillation is captured by both alpha and beta bands, in concordance with the high covariance of alpha and beta observed in our data, which the model corrects for using the interaction term. There also exists some evidence that the two bands together are directly linked to presentation of parkinsonian tremor [54]. Similar phenomena may also explain inclusion of the high gamma-HFO interaction in the LASSO model.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, several studies report a decrease in beta activity during parkinsonian tremor for reasons that are obscure. [49][50][51][52] Accordingly, it might be supposed that adaptive DBS should fail to treat parkinsonian tremor. The surprise is that this is only true in a minority of cases.…”
Section: What About Tremor?mentioning
confidence: 99%